Evaluation of fracture in mortar subject to tension loading using phase field model and three point bending test - Ge, Zhi; Wang, Yuanyuan; Hou, Yue; Sun, Wenjuan; Sun, Renjuan (Materials & design, 2015)
The Classic Fracture Mechanics (CFM) is the most widely used approach to study the initiation and propagation of cracks, which has the limitations in numerical simulations due to complex topological changes and possible singularity. To overcome its limitations, the Phase-Field Model (PFM) is presented to model the cracking failure in mortar subject to pure tension loading (Mode I) with different water/cement ratio and thickness. The mortar cracking surfaces are described using a phase-field variable which assumes one in the intact region and negative one in the crack region. The new white noise term is added into the classical Phase-Field Model to reflect the quasi-brittle cracking behavior of mortar. The non-conserved Allen-Cahn dynamics is then employed to simulate the growth of cracks. To verify the simulation results, three point bending test is conducted. It is discovered that the crack initiation and propagation in our simulation agrees very well with the experimental results.